2005
DOI: 10.1093/aob/mci262
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Features and Ultrastructure of Deschampsia antarctica (Poaceae) Leaves from Different Growing Habitats

Abstract: The anatomical and ultrastructural features of the leaf and their changes under stress conditions are considered in relation to the adaptations of D. antarctica to the climate conditions in the Maritime Antarctic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 31 publications
8
63
1
Order By: Relevance
“…It seems that salt-induced anatomical changes differed between plant species. For example, similarly to our data, Giełwanowska et al (2005) observed large IS and irregular mesophyll cells in Deschampsia antarctica plants grown in habitats exposed to high salinity and flooding. On the contrary, Arbutus unedo after 16 week-salt-treatment (52 and 105 mM NaCl) showed a reduction of mesophyll IS and an increase in cell size of the second layer of PM (Navarro et al, 2007).…”
Section: Leaf Anatomysupporting
confidence: 92%
“…It seems that salt-induced anatomical changes differed between plant species. For example, similarly to our data, Giełwanowska et al (2005) observed large IS and irregular mesophyll cells in Deschampsia antarctica plants grown in habitats exposed to high salinity and flooding. On the contrary, Arbutus unedo after 16 week-salt-treatment (52 and 105 mM NaCl) showed a reduction of mesophyll IS and an increase in cell size of the second layer of PM (Navarro et al, 2007).…”
Section: Leaf Anatomysupporting
confidence: 92%
“…These outgrowths are reminiscent of the stroma-filled tubular extensions of the plastid envelope membrane (stromules) described in the tissues of higher plants (Kwok & Hanson, 2004 for a review). Plastid protrusions and ⁄ or stromules have been reported in response to abiotic stresses, for example salt stress in the grass Deschanmpsia antartica (Gielwanowska et al, 2005) and high temperatures in Arabidopsis (Holzinger et al, 2007).…”
Section: Mitochondria and Plastidsmentioning
confidence: 99%
“…The soil and root samples, with ten replicates in each area, were collected from the rhizospheric region of Deschampsia antarctica Desv., an endemic species in this region, that occur from the coast of the island to the highest areas near the bare rock or in ice formations (Gielwanowska et al 2005, Gonçalves et al 2008.…”
Section: Methodsmentioning
confidence: 99%